The Relationship Between Family Support and Assertiveness with Drug Use Behavior - Abbas, Miranda; Noviekayati, IGAA; Santi, Dyan Evita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to examine the relationship between family support and assertiveness with the tendency to use narcotics in early adulthood. The univariate results show that family support has an average score of 2.591, indicating a high level of family support. Family support, particularly in the forms of emotional, esteem, and instrumental support, was found to play a significant role in preventing drug abuse, with a t-test yielding a t-value of 4.103 (p < 0.05). Meanwhile, assertiveness also had a high average score (2.573) and significantly influenced the tendency to use narcotics, with a t-value of 5.051 (p < 0.05). The multivariate analysis results indicate a significant interaction between both variables, with an F-value of 336.378 (p < 0.05), suggesting that family support and assertiveness together can reduce the tendency to use narcotics. The study concludes that the combination of positive family support and high assertiveness can strengthen an individual's protection against the risk of narcotic abuse in early adulthood.